Children’s perceptions of community outdoor spaces: a thematic analysis based on qualitative evidence from Hefei, China - Wei, Xiaohui; Abdul Malek, Nurhayati; Mohamed Ali, Salina (Universiti Teknologi Mara Cawangan Pulau Pinang, 2026)
This study explores how children aged 10–14 in Hefei, China, experience and interpret outdoor spaces in their neighbourhoods. Although childfriendly urban planning has received increasing attention, existing research on community outdoor spaces in China has largely focused on adult-centred perspectives, with limited attention given to children’s own perceptions and experiences. Semi-structured interviews were conducted with 20 children and analysed using NVivo-assisted thematic analysis within a qualitative research framework. The findings show that children understand community outdoor spaces through a combination of safety, comfort, enjoyment, accessibility, contact with nature, and expectations for future improvement. Six interconnected themes were identified: safety, comfort, fun, accessibility, naturalness, and future expectations. These themes influence children’s decisions about where to go, how long to stay, and whether a space feels inviting or restrictive. Overall, the results highlight how the design and management of community spaces shape children’s outdoor experiences, providing empirical support for more child-centred and nature-oriented community planning.